Analysis of Limb Explosive Performance of Elite Water Ski and Wakeboard Athletes: A Comparative Study - Uzizatun Maslikah; Fahmy Fachrezzy; Mansur Jauhari; Arga Nurcahya; Haris Nugroho (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This research uses the Survey Research Method, a quantitative research type approach meaning research that is comparative or different. The population and sample in this study were water skiers and wakeboard athletes as many as 30 people consisting of male and female athletes. Data collection techniques using tests and measurements: physical condition tests; For leg muscle explosiveness by using a vertical jump measuring instrument and a chronojump. Data analysis using quantitative descriptive analysis techniques, overall The data analysis technique used is a t-test at a significant level of 5%. To obtain the results of this study, which one better results from the explosive power of leg muscles in Water Ski and Wakeboard Athletes of DKI Jakarta Province using Vertical jump and Chronojump? The results of this study showed that: There was a difference in leg explosive power in terms of the use of vertical jump and chronojump tools in  Water Ski and Wakeboard athletes with an average value between the two groups, wherein the vertical jump group with an initial test average value of 47.50,  the chronojump group with an average value of 27.97. This means that the vertical jump group is better than the chronojump group. However, further research is needed related to the environmental, psychosocial, and psychological factors of athletes and those related to improving athlete performance.